Functional beliefs and risk minimizing beliefs among Thai healthcare workers in Maharaj Nakorn Chiang Mai hospital: Its association with intention to quit tobacco and alcohol - Surin Jiraniramai (2018)
© 2017 The Author(s). Background: Individual health beliefs are likely to play a key role in how people respond to knowledge and information about the potential harm from smoking and alcohol abuse. The objectives of the study were to 1) explore whether functional beliefs and risk minimizing beliefs were associated with intention to quit smoking and confidence to quit smoking and 2) explore whether functional beliefs and risk minimizing beliefs were associated with intention to quit alcohol drinking and confidence to quit alcohol drinking. Methods: A cross-sectional survey was conducted in 2013 among health care workers working in Thailand. Using predicted factor scores from factor analysis, the relationship between factor scores for each of the two beliefs and intention to quit and confidence to quit were tested using ANOVA and further adjusted for age and sex using linear regression. Results: Functional beliefs were inversely associated with the intention to quit and confidence to quit smoking. Both functional beliefs and risk minimizing beliefs were each inversely associated with the intention to quit and confidence to quit alcohol drinking. Conclusion: Our study enhances the understanding of the complexities of health beliefs regarding these two commonly abused substances. As functional beliefs were associated with smoking and alcohol use, interventions to counter the cultural values and individual beliefs about the benefits of smoking and alcohol use are needed. Tackling risk minimizing beliefs by providing individualized feedback regarding harm may also be useful in alcohol drinkers.